Implementation of STEM Learning with a Scientific Approach to Improving Critical, Creative Thinking, and Learning Outcomes - Yeti Komalasari; Minulya Eska Nugraha; Sudarwan Danim; Ahmad Zabidi Abdul Razak (Jurnal Pendidikan IPA Indonesia, 2024)
This research investigates the potential impact of implementing STEM learning with a scientific approach to improve critical thinking, creative thinking, and learning outcomes for Aviation Rescue and Firefighting cadets in the first aid course. Data analysis was performed using quantitative experimental and correlation analysis. The data was processed using IBM SPSS software with the Manova test, n-gain score, and correlation test. The sample in this research consisted of 45 cadets. The results of the MANOVA test show a significance value of 0.032 < 0.05, so the null hypothesis is rejected, and the alternative hypothesis is accepted. The n-gain scores of critical thinking show sixteen with medium criteria and seven with high criteria. The n-gain scores of creative thinking show seventeen with medium criteria and six with high criteria. The n-gain scores of learning outcomes show fifteen with medium criteria and eight with high criteria. The significance value of the correlation test is 0.000 < 0.05, so the null hypothesis is rejected, and the alternative hypothesis is accepted. This research concludes that STEM learning with a scientific approach influences critical thinking, creative thinking, and learning outcomes in the First Aid course. There is a correlation between STEM learning with a scientific approach and critical thinking, creative thinking, and learning outcomes in the first aid course.